Eye Tracking in Neuropsychological Research of Visual Gnosis Features in Children with Hearing Impairment - Y.K. Smirnova; Ju.E. Grigorova; L.N. Gordeeva (Клиническая и специальная психология)
The article is devoted to the problem of assessing the state of visual gnosis in children with hearing impairment in order to identify possible mechanisms for compensating for uneven development of mental functions and assessing the possibilities of remedial education. We combined the research potential of the classical neuropsychological approach with the eye-tracking methodology in order to study in detail through eye movements the uneven development of auditory, visual and verbal functions in information processing in children with hearing impairment. The task was to conduct not only a classical neuropsychological assessment of visual gnosis in children with hearing impairment, but also to obtain new data on eye tracking during neuropsychological tests. The study involved cochlearly implanted preschoolers with hearing impairment (N=15) and typically developing preschoolers (N=16) aged 5 to 7 years (M=6.1; SD=0.5). At the first stage, classical neuropsychological tests for visual gnosis were conducted, at the second stage, eye tracking was used to record eye movements during neuropsychological tests by preschoolers. Our study confirms the weakness of visual information processing processes during neuropsychological tests in children with hearing impairment. Analysis of eye movement strategies recorded by the eye tracker during neuropsychological tests allowed us to identify a number of features of visual information processing in children with hearing impairment: chaotic search, changes in the recognition sequence, decreased noticeability (“recognizability”) of images or decreased interest (duration of fixations and viewing), weakness of the holistic strategy and synthesis, fragmentation of perception. The duration of the scanning path, spatial density of fixations, scanning regularity, and scanning direction during image recognition differ. Features of the visual search strategy are observed in the number of switches, fixation time, and patterns of gaze transitions between areas of interest. In children with impairments, when performing tests for visual gnosis, an increase in the time of fixations is recorded, which indicates the cognitive complexity of perception. The combination of weakness in the processing of auditory and visual information leads to diffuseness, incorrectness of the correlation of the image of an object and its verbal designation due to the poverty of the vocabulary of children with hearing impairments.